Estudo dos limiares auditivos em altas freqüências em adultos - Lopes, Leila Quadrado (2005)
The present study aimed at applying high frequency audiometry in the frequency range from 9.000 to 20.000 Hz in individuals, in order to verify if ear, gender and age are variability sources. Method: There were selected 65 individuals (130 ears), being 22 male and 43 female in the age ranging from 20 to 60 years old, with no otological past, with normal tympanometric curves and hearing thresholds in pure tone conventional audiometry (250 8.000 Hz) and presence of acoustic reflexes. The audiometer used was a Grason Stadler GSI 61 with the Senheiser HAD-200 earphones, which allowed dB hearing threshold level. Results: there were no statistically significant differences between tested ears; there were statistically significant differences between age range, being worse the hearing thresholds with the increasing age, as well as there were statistically significant differences between hearing thresholds of female and male individuals, in which women has presented worse hearing thresholds only in 16.000 and 18.000 Hz. Nevertheless, in the other frequencies, there was a tendency of improving the hearing thresholds for female individuals. Conclusion: Despite of this procedure has not being used in the clinical routine, by evaluating the high frequencies thresholds we can get more information about the hearing system, increasing its comprehension and also providing more chances of a more precise prognostics about hearing lesions